Sound absorption and thermal insulation characteristics of fabrics made of pure and crossbred sheep waste wool. (March 2021) - Ghermezgoli, Zahra Mohammadi; Moezzi, Meysam; Yekrang, Javad; Rafat, Seyed Abbas; Soltani, Parham; Barez, Fred
Abstract: Waste wool fiber is a potential source for thermal and acoustical applications due to its natural properties. This work aims to investigate the potential of crossbreeding for the engineering of the sound absorption and thermal insulation properties of the waste wool. At first, a crossbreeding strategy was performed on the local sheep called Ghezel (Gh) thick-wool with Arkharmerino (Ar) fine-wool, and the procedure was continued up to two races (ArGh1 and ArGh2). Afterward, the wool fibers were collected from all four breeds, and the short fibers were removed as the waste. The chemical and morphological analyses were carried out on the fibers. The waste fibers were then spun and used as weft yarns to weave the woolen fabrics. The sound absorption and thermal insulation properties of the fabrics were also investigated. Additionally, the frequency-dependent sound absorption coefficient (SAC) of samples was predicted using the Mechel model. The results showed that the crossbreeding of Gh with Ar results in improvement of fiber fineness, which in turn positively affects the sound absorption behavior of the fabrics. There was a good adoption between the experimental and predicted results, indicating the high accuracy of the Mechel model for the woolen woven fabrics. The results also indicated that fabrics made from coarser fibers show better thermal insulation performance. The results indicated that waste wool as an environmentally friendly thermal insulation material has comparable acoustical and thermal characteristics to mineral/wools and glass fiber-based materials, with the advantage of being ecological and simultaneously economical, biodegradable, and abundant. Highlights: Waste wool has comparable acoustical and thermal characteristics to mineral wools. Fabrics made from waste wool can be used as a cover for lofty nonwoven fabrics. Crossbreeding is an effective strategy to engineer acoustic and thermal properties. Finer fibers provide higher sound absorption and lower thermal resistance.